Accounting for refrigeration heat exchange in energy performance simulations of large food retail buildings. (May 2017) - Parker, James; Glew, David; Fletcher, Martin; Thomas, Felix; Gorse, Christopher
Heat exchange between chilled food storage and conditioned spaces in large food retail stores is not currently required as part of design stage regulatory compliance energy performance models. Existing work has identified that this exchange has a significant impact on store energy demand and subsequently leads to unrealistic assessment of building performance. Research presented in this article uses whole building dynamic thermal simulation models that are calibrated against real store performance data, quantifying the impact of the refrigeration driven heat exchange. Proxy refrigerated units are used to simulate the impact of these units for the sales floor areas. A methodology is presented that allows these models to be simplified with the aim of calculating a realistic process heat exchange for refrigeration and including this in thermal simulation models; a protocol for the measurement of chilled sales areas and their inclusion in the building models is also proposed. It is intended that this modelling approach and the calculated process heat exchange inputs can be used to improve the dynamic thermal simulation of large food retail stores, reduce gaps between predicted and actual performance and provide more representative inputs for design stage and regulatory compliance energy calculations. Practical application: The modelling methodology and research findings presented in the article are of practical use for building energy modelling engineers using dynamic simulation models to design and/or evaluate the energy performance of large food retail stores. The methodology can be used in the design of new facilities or the evaluation of large scale retrofit projects. It is also of practical interest to energy and facility managers within large food retail organisations as it will aid their understanding of applied energy performance models.